Perbandingan Metode Interpolasi Newton dan Lagrange dengan Bahasa Pemrograman C++ - Yoga Furqaansyah; Fauziah Fauziah; Agus Gunaryati; Iskandar Fitri (KITA Institute, 2022)
Interpolation is defined as an estimate of a known value. Extensive interpolation is an attempt to determine the approximate value of an analytic function that is unknown or alternatively a complex function whose analytic equation cannot be obtained. You can combine the use of math and math to analyze the price of an item. This study describes Newton's method and the polynomial method. Therefore, interpolation with Newton's method has an error value that is smaller than the error value of the Lagrange interpolation. The results in this research case study when x = 2.5 using 10 data performed using Newton's polynomial interpolation method have a result of 1.70956 where this value is lower than the value of the analysis using the Lagrange method which is 3.2163.